CORRELATION BETWEEN KNOWLEDGE AND BEHAVIOR OF USING VITAMIN C SUPPLEMENTS AMONG HEALTH AND NON-HEALTH STUDENTS IN CENTRAL JAVA DURING THE COVID-19 PANDEMIC - Isnaini Nur Jannah; Eva Annisaa'; Intan Rahmania Eka Dini (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2023)
Background: During the COVID-19 pandemic, 57.1% of students used vitamin C. Everyone's behavior/actions in using vitamin C are different. This is influenced by several factors, one of which is knowledge. Objective: Knowing the differences in the level of knowledge and the different levels of behavior in using vitamin C supplements and the correlation between knowledge and behavior in using vitamin C supplements among health and non-health students in Central Java. Methods: Cross sectional analytic research using a questionnaire with purposive sampling technique. Data were analyzed using Chi-Square difference test and Rank Spearman correlation test. Results: The level of knowledge of health students related to vitamin C was in the good category (75%) and non-health students was in the sufficient category (42%). The behavior level of health students related to the use of vitamin C was in the good category (83.3%) and non-health students was in the poor category (58%). Chi-Square test showed that there were differences in the level of knowledge and behavior in using vitamin C between health students and non-health students with a p value = 0.000. There was a correlation between knowledge and the behavior of using vitamin C with a p value = 0.000. The Spearman correlation coefficient (r) obtained was 0.612. Conclusion: There were differences in the level of knowledge and different levels of behavior between health students and non-health students. There was a correlation between knowledge and behavior in using vitamin C supplements among health and non-health students in Central Java.